SKILLS IMPROVING PROCEDURE TEXT WRITING THROUGH THE NUMBERED HEAD TOGETHER (NHT) TYPE LEARNING MODEL IN THE FIRST MIDDLE SCHOOL STUDENT - Gea, Evaluasi (Al'adzkiya International of Education and Sosial (AIoES) Journal, 2020)
The purpose of this study is to improve students' skills in writing procedural texts using the Inquiry learning model. This research is a classroom action research. This research activity was carried out in two cycles using data collection techniques, observation sheets, and assessment sheets. Data were analyzed in three stages, namely data reduction, data exposure, and conclusions. From the results of this study, it is evident that there is an increase in the skills of students in writing procedural texts using the numbered head together (NHT) type learning model in cycle I, with an average value of 59,16% and cycle II, with an average value of 80,65%.